Understanding Experimental Economics - Nielsen, Carsten S.; Sebald, Alexander C.; Webb, Edward J.D. (Politik, 2014)
Experiments have become a well-established methodological tool in economics. e development of experi- mental economics and the diversi cation of experimental methods have equipped economists with new and powerful means of scienti c investigation. eir worth is readily demonstrated in the exciting and promising results they have produced, and will continue to produce. Against the background of this success story, our selective discussion critically highlights four important aspects of experimentation in economics. We concen- trate on the role and importance of material incentives, potentially confounding experimenter demand e ects and strategies to minimise these, the no deception rule as well as the issue of external validity.